Parental Stress and Childhood Cancer in Libya: A Cross-Sectional Study in Misurata (Razi Medical Journal, 2025)
Children worldwide continue to be impacted by both chronic and acute diseases. Although there has been a huge improvement in survival rates in the last decades, the psychosocial impact of childhood cancer cannot be underestimated. This study aims to determine the prevalence of cancer-related stress among parents of children undergoing cancer treatment in Misurata, Libya. A cross-sectional survey by the Perceived Stress Scale 10-items (PSS-10) was conducted between March 21, 2023, and January 15, 2024, among the parents caring for children diagnosed with cancer, and parents who care for children without cancer. In this study, 597 respondents were included in the analysis: 364 mothers (61%), and 233 fathers (39%). The mean (SD) age of the respondents (587/597) was 38.12 (8.46). The stress symptoms, which were assessed using the PSS-10 scale, had a mean (SD) score of 17.58 (6.6), and the following categories were identified: low stress (0–13) 169 (28.3%); moderate stress (14–26) 368 (61.6%); and severe stress (27–40) 60 (10.1%). A statistically significant association was found between stress symptoms and the following variables: parents (χ2= 23.7, p
Keywords: Parental Stress, Childhood Cancer, Prevalence, Libya, Cross-sectional Study.